THE UNCONSCIOUS MEMORIES OF LOSING AS THE TRIGGER FACTOR OF SELF DEFENSE MECHANISMS IN THE NOVEL PLEASE LOOK AFTER MOM BY KYUNG-SOOK SHIN - Manik, Indah Novelina; Hafsah, Siti (Prologue: Journal on Language and Literature, 2024)
This research explores the unconscious that is reflected in the unconscious memories of loss in the novel Please Look After Mom by Kyung-Sook Shin. There are two objectives of this research: 1) To find out the form of unconscious memory contained in the novel "Please Look After Mom" by Kyung-Sook Shin, and 2) To explain how unconscious memory triggers the self-defense mechanism that describes the psychological in the novel "Please Look After Mom" by Kyung-Sook Shin. In analyzing the data, the researcher uses the theory of Psychoanalysis by Carl Jung to find out the forms of unconscious contained in the novel, then the researcher analyzes and explains the data from the novel. The methodology in this study is a qualitative research by taking data from quotations in the novel which the researcher then conveys descriptively. The results of this study, the researchers found that the forms of unconsciousness in Kyung-Sook Shin's novel Please Look After Mom are the collective unconscious and the personal unconscious. And self-defense mechanisms that affect memories are persona, shadow, great mother, which arise due to the things that trigger the loss.